The option value of vacant land: Don't build when demand for housing is booming - Rutger-Jan Lange; Coen N. Teulings (Tinbergen Institute, 2021)
Urban structures and urban growth rates are highly persistent. This has far-reaching implications for the optimal size and timing of new construction. We prove that rational developers postpone construction not because prospects are gloomy, but because they are bright. The slow mean reversion in urban growth rates for the Netherlands and the United States (estimated at 0.07 per annum) implies that a substantial share of cities should optimally postpone construction due to high growth. Observed heterogeneity in floorspace density across cities can be explained not by differences in population levels, but in growth rates.
Keywords: D81; G12; R14; R31; R51; 330; irreversible investment; mean-reverting growth; real-estate construction; real options; urban growth